2020
DOI: 10.1038/s41598-020-66652-z
|View full text |Cite
|
Sign up to set email alerts
|

Combination of preoperative tumour markers and lymphovascular invasion with TNM staging as a cost and labour efficient subtyping of colorectal cancer

Abstract: Tumour-Node-Metastasis (TNM) staging of colorectal cancer (CRC) needs further classification for better treatment because of disease heterogeneity. Although molecular classifications which are expensive and laborious are under study, cost and labour efficient subtyping is desirable. We assessed the combinations of preoperative tumour marker (TM) elevation and tumour lymphovascular invasion (LVI) as a solution. We used the pooled data of 7151 colon cancer (CC) patients and 4620 rectal cancer (RC) patients who r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Vascular invasion is a remarkable risk factor of recurrence (OR 2.3 (CI 95%; 1.56 -3.4)). This finding is in line with previous findings indicating vascular invasion as an important factor in determining high-degree risk factors and a favorable treatment strategy if assessed with tumor markers (TM-LVI status) (20,21). T stage and N stage are also considered risk factors with OR 2.27 (CI 95%; 1.14 -4.51) and OR 2.56 (CI 95%; 1.41 -4.62), respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Vascular invasion is a remarkable risk factor of recurrence (OR 2.3 (CI 95%; 1.56 -3.4)). This finding is in line with previous findings indicating vascular invasion as an important factor in determining high-degree risk factors and a favorable treatment strategy if assessed with tumor markers (TM-LVI status) (20,21). T stage and N stage are also considered risk factors with OR 2.27 (CI 95%; 1.14 -4.51) and OR 2.56 (CI 95%; 1.41 -4.62), respectively.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that simple TNM staging lacks a certain accuracy in predicting the prognosis of intermediate colorectal tumors, and some studies have also proposed the same argument. [36][37][38] For example, A 2020 study evaluated the effect of preoperative tumor markers (TM) combined with LVI (TM-LVI) levels on relapse-free survival at different TNM stages. The c-index and Akaike's information criterion were used to select the best-matched subtypes for predicting relapse-free survival.…”
Section: Discussionmentioning
confidence: 99%
“… Yamagata et al (2021) . reiterated that the presence of LVI was a crucial prognosticator in lymph node-positive breast cancer patients ( Yamano et al, 2020 ). Our study also demonstrated that the DFS and OS of breast cancer patients with LVI were lower in contrast to those without LVI.…”
Section: Discussionmentioning
confidence: 99%